Did politicians use non-public macroeconomic information in their stock trades? Evidence from the STOCK Act of 2012 - Serkan Karadas; Minh Tam Schlosky; Joshua C. Hall (Journal of Risk and Financial Management, 2021)
Existing research shows that members of Congress made informed trades prior to the passage of the STOCK Act of 2012. There is also evidence in the literature to suggest that the STOCK Act was able to deter politicians from trading based on non-public information. However, the question of whether politicians made informed trades at the market level (using non-public macroeconomic information, not just firm-specific information) in the first place and whether they continued to do so even after the passage of the STOCK Act remains unexamined. We analyze 101,191 individual stock transactions covering the 2004-2014 period and find that the STOCK Act adversely affected the ability of politicians' aggregated stock trades to predict the stock market returns. Our results imply that politicians used non-public macroeconomic information prior to the STOCK Act, and this legislation was influential in deterring politicians from using non-public macroeconomic information in their stock trades. Our findings also provide input on the current debate on the need for the STOCK Act 2.0.
Keywords: G12; G14; G18; D72; D73; 330; informed trading; non-public information; politicians; STOCK Act